PENERAPAN BIMBINGAN KELOMPOK DENGAN TEKNIK BRAINSTORMING UNTUK MENINGKATKAN KETERBUKAAN DIRI DALAM KOMUNIKASI PADA SISWA MAN KOTA PALANGKA RAYA - Sri Mariana; Y. Bunu, Helmuth; Feronika, Nopi (Jurnal Bimbingan dan Konseling Pandohop, 2021)
Self-disclosure is the process of giving the other party the opportunity to know how we think, how we feel about something, and about our desires. Students who are capable of self-openness are proven to be able to adjust, be more confident, have a positive attitude, be more objective, and open. The purpose of this study is to determine the extent to which brainstorming techniques are used to assist students in increasing self-disclosure in communication among students of MAN Palangka Raya City. The type of research used is Pre-Experimental Designs with One-group Pretest-Postets Design. The sampling technique in this study was carried out by purposive sampling. The sample in this study was 6 students of MAN Kota Palangka Raya who have low self-disclosure in communication. The data collection tool uses a self-disclosure questionnaire in communication. Meanwhile, the data analysis technique used is non-parametric statistics with paired two-sample t-test formula. The results of the study show self-openness in communication before receiving group guidance with the brainstorming technique of 50% in the low category, after receiving group guidance with the brainstorming technique of 69% with the high category. The difference in the level of self-disclosure in communication before and after being given group guidance with brainstorming techniques was 18%. The results of the paired two-sample t-test obtained t count-12.548 and t table -2.015 means that Ha is accepted. These results indicate that the brainstorming technique is so effective in increasing self-disclosure in communication among students of MAN Kota Palangka Raya.